Theories of Fairness and Reciprocity. Evidence and Economic Applications - Ernst Fehr; Klaus M. Schmidt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2001)
Most economic models are based on the self-interest hypothesis that assumes that all people are exclusively motivated by their material self-interest. In recent years experimental economists have gathered overwhelming evidence that systematically refutes the self-interest hypothesis and suggests that many people are strongly motivated by concerns for fairness and reciprocity. Moreover, several theoretical papers have been written showing that the observed phenomena can be explained in a rigorous and tractable manner. These theories in turn induced a new wave of experimental research offering additional exciting insights into the nature of preferences and into the relative performance of competing theories of fairness. The purpose of this paper is to review these recent developments, to point out open questions, and to suggest avenues for future research.
urn:nbn:de:bvb:19-epub-14-5
Keywords: C7; C9; D0; J3; 330; Behavioral Economics; Fairness; Reciprocity; Altruism; Experiments; Incentives; Contracts; Competition